The model manual everything you need to know about modelling - Morris, Sandra (Weidenfeld & Nicolson, 1997)
This is an insider's guide to the world of modelling, from fashion to child modelling, and from glamour to character work. It shows readers the best way to go about becoming a model, from the initial enquiry to the contract and provides an international index of agencies for all types of model.